The current status of Aureobasidium pullulans in biotechnology - Prasongsuk, Sehanat; Lotrakul, Pongtharin; Ali, Imran; Bankeeree, Wichanee; Punnapayak, Hunsa (Folia microbiologica, 2018)
Different strains of the saprophytic yeast-like fungus Aureobasidium pullulans (Ascomycota: Dothideales) exhibit different biochemical characteristics, while their ubiquitous occurrence across diverse habitats and environmental conditions makes them an easily accessible source for biotechnological exploitation. They are useful in agricultural and industrial applications. Their antagonistic activities against postharvest pathogens make them suitable bioagents for the postharvest preservation of fruits and vegetables, while they possess antimicrobial activities against bacteria and fungi. Additionally, A. pullulans appears to be a potent source of single-cell protein. Many strains of A. pullulans harbor a wide range of industrially important enzymes, while the trademark exopolysaccharide pullulan that they produce has been extensively studied and is currently used in many applications. They also produce poly (β-L-malic acid), heavy oil liamocins, siderophore, and aubasidan-like β-glucan which are of interest for future applications. Ongoing studies suggest that A. pullulans holds many more interesting properties capable of further potential biotechnological applications.
Keywords: Ascomycota; Glucans; Fungal Proteins; glukany; Industrial Microbiology; fungální proteiny; průmyslová mikrobiologie